An Overview of Technology Landscape in Construction Materials for the Indonesian Construction Industry - Rani G. K. Pradoto; Biemo Woerjanto Soemardi; Abdhy Gazali; Hintama Nathaniel Sunarjo; Andira Triana Putri; Rika Permatasari Purba; Ignatius Mahardika (Jurnal Teknik Sipil, 2023)
Abstract.  The Indonesian construction sector plays a substantial role in the nation's economic growth. According to the World Economic Forum, this industry currently contributes approximately 6% to the global GDP and is projected to increase to 14.7% by 2030. Nevertheless, the construction sector predominantly relies on traditional craft-based methods, resulting in suboptimal performance and quality due to limited technology utilization. Hence, the Indonesian construction industry must increase investment in technology adoption, development, and application to enhance national development support. Material technology plays an essential role in construction projects. A survey of 40 Indonesian contractors revealed that the utilization priority for concrete and steel materials remains high under normal conditions and during the covid-19 pandemic. This study aims to provide a comprehensive overview of the historical development, utilization, contribution, and future strategy for concrete and steel construction material technology in Indonesia. Contrastingly, this data is crucial for shaping construction technology development and utilization policies in Indonesia. The study will systematically chart the technological landscape in the country, employing literature reviews, interviews, and questionnaires as its methodology. Keywords: Material technology, technology development, technology utilization. Abstrak. Sektor konstruksi Indonesia memainkan peran penting dalam pertumbuhan ekonomi negara ini. Menurut World Economic Forum, industri ini memberikan kontribusi sekitar 6% terhadap Produk Domestik Bruto (PDB) global dan diperkirakan akan meningkat menjadi sekitar 14,7% pada tahun 2030. Namun, sektor konstruksi masih sangat mengandalkan metode tradisional, yang mengakibatkan kinerja yang kurang optimal dan kualitas yang rendah karena rendahnya penggunaan teknologi. Oleh karena itu, industri konstruksi Indonesia harus meningkatkan investasi dalam adopsi, pengembangan, dan penerapan teknologi untuk meningkatkan dukungan pengembangan nasional. Teknologi material memainkan peran penting dalam proyek konstruksi. Sebuah survei terhadap 40 kontraktor Indonesia mengungkapkan bahwa prioritas pemanfaatan material beton dan baja tetap tinggi dalam kondisi normal dan selama pandemi covid-19. Studi ini bertujuan untuk memberikan gambaran menyeluruh tentang perkembangan historis, pemanfaatan, kontribusi, dan strategi masa depan untuk teknologi material konstruksi beton dan baja di Indonesia. Sebaliknya, data ini krusial dalam kebijakan pengembangan dan pemanfaatan teknologi konstruksi di Indonesia. Studi ini akan secara sistematis menggambarkan lanskap teknologi di negara ini, dengan menggunakan studi literatur, wawancara, dan kuesioner sebagai metodologi utamanya. Kata-kata kunci: Teknologi material, pengembangan teknologi, pemanfaatan teknologi.